2020
DOI: 10.1111/liv.14518
|View full text |Cite
|
Sign up to set email alerts
|

Functional rescue of an ABCB11 mutant by ivacaftor: A new targeted pharmacotherapy approach in bile salt export pump deficiency

Abstract: Background & Aim: The canalicular bile salt export pump (BSEP/ABCB11) of hepatocytes is the main adenosine triphosphate (ATP)-binding cassette (ABC) transporter responsible for bile acid secretion. Mutations in ABCB11 cause several cholestatic diseases, including progressive familial intrahepatic cholestasis type 2 (PFIC2) often lethal in absence of liver transplantation. We investigated in vitro the effect and potential rescue of a BSEP mutation by ivacaftor, a clinically approved cystic fibrosis transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
(114 reference statements)
2
18
0
Order By: Relevance
“…Recently, two teams have successfully demonstrated stable ABCB4 gene expression and correction of PFIC3 phenotype in a murine model using adeno-associated virus serotype 8 (AAV8)-mediated gene therapy [19,20]. Other studies have shown that molecular chaperones may be of therapeutic value in PFIC syndromes, including PFIC3 [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two teams have successfully demonstrated stable ABCB4 gene expression and correction of PFIC3 phenotype in a murine model using adeno-associated virus serotype 8 (AAV8)-mediated gene therapy [19,20]. Other studies have shown that molecular chaperones may be of therapeutic value in PFIC syndromes, including PFIC3 [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ivacaftor has also shown therapeutic potential in an in vitro model of progressive familial intrahepatic cholestasis type 2 (PFIC2) caused by ABCB11 missense mutations affecting bile salt export pump (BSEP): Ivacaftor treatment increased the taurocholate transport activity of mutated BSEP by 1.7-fold, reaching 95% of BSEP function [ 60 ].…”
Section: Effects Of Cftr Modulators On Cfldmentioning
confidence: 99%
“…To assess BSEP expression in liver thus may help predict prognosis and allow for improved personalized treatment. Also of help may be determinations of BSEP variant function in vitro 20 …”
Section: Discussionmentioning
confidence: 99%
“…Also of help may be determinations of BSEP variant function in vitro. 20 TNC may have been the first episode of BRIC in some of our patients, a possibility that in any individual can be excluded only with lifelong follow-up. Our study's brevity, with the shortest follow-up of only 1 year, thus constitutes a limitation in our work.…”
Section: F I G U R Ementioning
confidence: 91%